REFORMATION IN LEARNING HISTORY - Suranto, - (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2010)
Learning history in school have benefit for life and for the nation and state itself. Learning history can evoke a sense of history and national consciousness, but the reality that there is less functional and even become a boring subject. Various reformation efforts have been made, but has not shown significant result, therefore, necessary reforms. These reforms were carried out with a systemic reform, changing the mindset about learning the history and unite the steps of all parties concerned, including decision makers. Renewal in learning the history of applied learning model that develops students intellectually. Through this model of learning is expected to be more attractive and functioning properly.